2022
DOI: 10.1002/hep.32594
|View full text |Cite
|
Sign up to set email alerts
|

Change in serial liver stiffness measurement by magnetic resonance elastography and outcomes in NAFLD

Abstract: Background and Aims: The impact of disease progression in NAFLD on liver outcomes remains poorly understood. We aimed to investigate NAFLD progression using longitudinal liver stiffness measurements (LSM) by serial magnetic resonance elastography (MRE) and the association with liver outcomes. Approach and Results: All adult patients with NAFLD who underwent at least two serial MREs for clinical evaluation at Mayo Clinic, Rochester, between 2007 and 2019 were identified from the institutional database. Progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…[336,344] Changes in liver stiffness may also be useful in identifying disease progression, such that an increase in liver stiffness of 20% on either VCTE or MRE may be associated with disease progression and long-term clinical outcomes. [345,346] In identifying patients with cirrhosis, a sequential approach with a FIB-4 > 3.48 and LSM by VCTE ≥ 20 kPa had a specificity of 90%. [4] However, such an approach will likely miss some patients with cirrhosis due to low sensitivity of these cut points.…”
Section: Elastographymentioning
confidence: 99%
“…[336,344] Changes in liver stiffness may also be useful in identifying disease progression, such that an increase in liver stiffness of 20% on either VCTE or MRE may be associated with disease progression and long-term clinical outcomes. [345,346] In identifying patients with cirrhosis, a sequential approach with a FIB-4 > 3.48 and LSM by VCTE ≥ 20 kPa had a specificity of 90%. [4] However, such an approach will likely miss some patients with cirrhosis due to low sensitivity of these cut points.…”
Section: Elastographymentioning
confidence: 99%
“…To date, there are limited data on the association between change in MRE and change in liver histology in cohorts of 50–100 patients 23,41 . A recent study evaluated the impact of change in MRE on liver-related outcomes and demonstrated that progression in LS on MRE in 29 patients with compensated cirrhosis was associated with hepatic decompensation or death 42 . Future studies may evaluate if serial MRE measurements over time can refine the prediction of future liver-related events, although the clinical value of accurate risk prediction with a single MRE value remains significant.…”
Section: Discussionmentioning
confidence: 99%
“…[23,41] A recent study evaluated the impact of change in MRE on liver-related outcomes and demonstrated that progression in LS on MRE in 29 patients with compensated cirrhosis was associated with hepatic decompensation or death. [42] Future studies may evaluate if serial MRE measurements over time can refine the prediction of future liver-related events, although the clinical value of accurate risk prediction with a single MRE value remains significant. Second, primarily because MRE has become available in the clinical practice more recently compared with other noninvasive tests, for example, VCTE or other blood-based markers, our study has a relatively short median follow-up duration.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A 15% increase in the LS value measured by MRE was associated with histologic fibrosis progression and progression from early to advanced liver fibrosis. A retrospective study of 128 patients with NAFLD who underwent at least two serial MRE examinations showed a significantly higher risk of the development of cirrhosis and decompensation or death in patients with a ≥19% increase in LS value from baseline than in those without [ 80 ].…”
Section: Role Of Noninvasive Tests In Disease Monitoringmentioning
confidence: 99%